Body mass index, as a novel predictor of hepatocellular carcinoma patients treated with Anti-PD-1 immunotherapy - Chen, Jierong; Lu, Lianghe; Qu, Chunhua; A, Gari; Deng, Fangqi; Cai, Muyan; Chen, Wei; Zheng, Lie; Chen, Jiewei (Frontiers in Medicine, 2022)
Immunocheckpoint inhibitors have shown significant efficacy in the treatment of hepatocellular carcinoma (HCC), but there are individual differences. The aim of this study was to explore body mass index (BMI) as a predictor of anti-PD-1 efficacy in patients with HCC. We retrospectively analysed 101 HCC patients who treated with anti-PD-1 at Sun Yat-sen University Cancer Center from July 2018 to November 2019 and divided them into overweight (BMI>24.9) and non-overweight (BMI≤24.9) groups based on baseline BMI levels. BMI>24.9 accounted for 22 cases (21.8%) and BMI≤24.9 accounted for 79 cases (78.2%) in the study cohort. Overweight patients had higher disease control rates than non-overweight patients (P=0.019, respectively). The mean progression-free survival (PFS) in overweight patients (10.23 months) was significantly longer than that of non-overweight patients (6.85 months; P=0.027). Among patients with immune-related adverse events (irAEs), the mean PFS was also significantly longer in overweight patients (7.72 months) than in non-overweight patients (5.31 months, P=0.034). Multivariate analysis showed that BMI was an independent prognostic factor for PFS in HCC patients treated with anti-PD-1 (hazard ratio: 0.47, P=0.044). Thus, higher BMI predicts a better prognosis among HCC patients treated with anti-PD-1. In clinical practice, patients' BMI can provide a useful tool for predicting the efficacy of anti-PD-1 therapy.